2015
DOI: 10.1111/jam.12916
|View full text |Cite
|
Sign up to set email alerts
|

Safety and technological properties of bacteriocinogenic enterococci isolates from Tunisia

Abstract: This is one of very few studies that identified safe Enterococcus strains capable of producing a wide variety of enterocins against different spoilage and pathogenic micro-organisms that have good potential for application as adjunct/protective cultures in foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 55 publications
0
15
0
3
Order By: Relevance
“…Three isolates showed hemolytic activity but were cylA-free. Jaouani et al (2015) reported similar results and speculated that other lytic genes might be involved in the cytolysin expression.…”
Section: Systematic Safety Evaluation Of Isolates Of Enterococci Frommentioning
confidence: 53%
See 3 more Smart Citations
“…Three isolates showed hemolytic activity but were cylA-free. Jaouani et al (2015) reported similar results and speculated that other lytic genes might be involved in the cytolysin expression.…”
Section: Systematic Safety Evaluation Of Isolates Of Enterococci Frommentioning
confidence: 53%
“…Interestingly, 4 gelE-positive strains did not show gelatinase activity, and 4 clyA-positive strains did not show hemolytic activity. The silence of clyA and gelE has been reported frequently (Medeiros et al, 2014;Jaouani et al, 2015). Perin et al (2014) reported that different culture conditions could strongly influence the expression of clyA and gelE.…”
Section: Systematic Safety Evaluation Of Isolates Of Enterococci Frommentioning
confidence: 83%
See 2 more Smart Citations
“…For instance, in a recent study, Jaouani et al . () identified safe Enterococcus strains with suitable technological properties that can produce a wide variety of enterocins against pathogenic micro‐organisms. Moreover, many types of raw milk cheeses are still eaten fresh in many countries all over the world, such as ricotta, chevre, quark, cottage, queso fresco, Egyptian karish cheese and other Mexican‐style fresh cheeses (Hammed et al .…”
Section: Introductionmentioning
confidence: 99%